FLE, FLCA, and FL Perceived Competence and FL Learning Effort in Saudi Military Cadets: A Structural Equation Modeling Approach - Alqahtani, Ali (International Journal of Language and Literary Studies, 2025)
Using structural equation modeling, the present study takes the initiative to test a theoretical model that subsumes the following latent variables: Foreign Language Enjoyment (FLE), Foreign Language Classroom Anxiety (FLCA), foreign language (FL) perceived competence, and FL learning effort as the criterion measure. A total of 148 Saudi cadets at a Saudi military academy studying English as the only foreign language volunteered to complete a questionnaire survey. The study found that FLCA negatively impacted all the other latent variables in the proposed model. While the negative influence of FLCA on FL perceived competence was direct, FLCA indirectly contributed to FLE and FL learning effort. In addition, as FL perceived competence was negatively impacted by FLCA, it directly and positively contributed to FLE. Finally, FLE was the only latent variable that determined FL learning effort, i.e., the effort that these Saudi English learners reported they invested in learning English. The results of the present study are discussed in relation to the findings of previous studies in the field.